Sustainable performance measurement through digital transformation within the sustainable development framework: the mediating effect of supply chain concentration - Sun, Le; Ong, Tze San; Teh, Boon Heng; Di Vaio, Assunta (John Wiley and Sons, 2024)
This study establishes a conceptual framework, “digital transformation – supply chain concentration – sustainable performance”, to address the existing knowledge gap and elucidate the nuanced connections between digital transformation, supply chain concentration, and sustainable performance. Indeed, the existing body of literature does not offer detailed analyses of the pathways and effects concerning the interplay among the three dimensions within the sustainable development framework. The model's foundation is rooted in stakeholder theory. By examining a sample of 3947 listed Chinese firms, this study's results highlight a noteworthy link between digital transformation and enhanced sustainable performance, assessed through the triple bottom line framework, thus helping to achieve sustainable development goals (SDGs), such as the eighth and ninth SDGs. This improvement is attributed to reducing supply chain concentration and promoting a diversified supply chain configuration. Furthermore, the correlation between digital transformation and sustainable performance settings demonstrates significant heterogeneity. This study enhances stakeholder theory by demonstrating that digital transformation and supply chain concentration contribute to sustainable performance, supporting the eighth and ninth SDGs and offering managers a pathway for sustainable development. It also calls for policies that promote digital transformation and diversified supply chains to improve societal welfare and sustainability practices.